Geohazard features of the Tyrrhenian Calabria - Daniele Casalbore; Alessandro Conforti; Francesca Budillon; Eleonora Martorelli; Eleonora Morelli; Martina Pierdomenico; Alessandro Bosman; Giovanni De Falco; Gabriella Di Martino; Francesco Giseppe Falese; Sara Innangi; Renato Tonielli; et al. (Journal of Maps)
This paper accompanies the Maps of Geohazard features of the Cilento and the Calabro-Tyrrhenian continental margin in the southern Tyrrhenian Sea (Italy). The main geohazard-related features were derived from extensive seafloor mapping through the collection of high-resolution multibeam data acquired during several oceanographic cruises. They encompass many fluids seepage features, fault scarps, landslides scars, gullies, channels, and canyons. Hazards related to coastal landslides and shelf-indenting canyons are very high in these sectors (especially in southern Calabria) due to active seismicity coupled with rapid uplift, high sedimentation rates and narrow or totally absent continental shelf, thus promoting a direct connection between steep slopes and coastal areas. In this setting, mass-wasting features can directly impact coastal or submarine infrastructures or indirectly create local tsunami waves, as observed in historical times. Moreover, this physiographic setting of the margin facilitates the transfer of marine litter toward deep-sea areas.